The Overview of Knowledge and Attitudes of Young Women Regarding Breast Self-Examination (SADARI) in Kalimojosari Village - Azizah, Rifa; Natalya, Wiwiek (LPPM UNIKAL, 2025)
ABSTRACT Rifa Azizah1 , Wiwiek Natalya2 An Overview of Knowledge and Attitudes ofAdolescent Girls Regarding Breast Self- Examination (BSE) in Kalimojosari Village Introduction: Breast self-examination (BSE) is an important step in the early detection of breast-related diseases, particularly breast cancer. Data from the Global Cancer Observatory (GLOBOCAN) in 2020 indicated that breast cancer ranked first among cancer cases in Indonesian women, with approximately 65,858 new cases (30.8%). Unfortunately, a lot of women are still diagnosed late due to a lack of awareness of early detection. Knowledge and attitudes of adolescents towards BSE play a significant role informing healthy habits from an early age. Methods: This study used a descriptive quantitative design with 90 adolescent girls as respondents. Data were collected using a questionnaire that measured knowledge and attitude levels. Data analysis was conducted with univariate analysis to determine the frequency distribution of respondents’ knowledge and attitudes. Results: Most respondents, 70 individuals (77.8%),had good knowledge of BSE. In addition, almost allrespondents, 89 individuals (98.9%), demonstrated apositive attitude towards BSE. Conclusion: Most adolescent girls had good knowledge and a positive attitude towards BSE. Even respondents with lower knowledge levels mostly exhibited a positive attitude. Keywords: adolescent girls, attitude, BSE, knowledge References: 33 (2015-2024).